2016
DOI: 10.1523/jneurosci.3617-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Iron Level and Myelin Content in the Ventral Striatum Predict Memory Performance in the Aging Brain

Abstract: Age-related memory impairments have been associated with structural changes in the dopaminergic system, but the underlying mechanisms remain unclear. Recent work indicates that iron accumulation might be of particular relevance. As iron accumulates, a degeneration of myelin sheaths has been observed in the elderly, but the relationship between both and their impact on memory performance in healthy elderly humans remain important open questions. To address this issue, we combined an established behavioral parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 63 publications
(29 reference statements)
7
52
1
1
Order By: Relevance
“…Previous studies suggested that R2* values in the ventral striatum increase with aging as a result of iron accumulation, as observed by T 1 shortening. Although it is not easy to correlate specific brain structure changes with specific brain functions due to the heterogeneity of these structures, Steiger et al demonstrated that higher iron levels within the ventral striatum predicts memory performance . The nucleus accumbens is a part of the limbic circuit and is involved in both motivation and memory functions, which tend to decrease with aging.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies suggested that R2* values in the ventral striatum increase with aging as a result of iron accumulation, as observed by T 1 shortening. Although it is not easy to correlate specific brain structure changes with specific brain functions due to the heterogeneity of these structures, Steiger et al demonstrated that higher iron levels within the ventral striatum predicts memory performance . The nucleus accumbens is a part of the limbic circuit and is involved in both motivation and memory functions, which tend to decrease with aging.…”
Section: Discussionmentioning
confidence: 88%
“…36 A monotonous decline in T 1 relaxation time was observed in the nucleus accumbens in this study. Previous studies suggested that R2* values in the ventral striatum increase with aging as a result of iron accumulation, 26,37 as observed by T 1 shortening. Although it is not easy to correlate specific brain structure changes with specific brain functions due to the heterogeneity of these structures, Steiger et al demonstrated that higher iron levels within the ventral striatum predicts memory performance.…”
Section: Discussionmentioning
confidence: 90%
“…Data from this group of elderly participants have already been published (Steiger et al, 2016). This study was carried out in accordance with the recommendations of the local ethics committee (Medical Association Hamburg).…”
Section: Methodsmentioning
confidence: 99%
“…We took advantage of structural MRI data for all elderly (but not young) participants acquired in a separately conducted study using a 3T MR system (Siemens Trio) with a standard 32-channel head coil as described in Steiger et al (2016). Briefly, whole-brain multiparameter mapping (MPM; Draganski et al, 2011) was conducted on the basis of multi-echo 3D FLASH (fast low angle shot) images at 1 mm isotropic resolution with predominantly proton density (PD), magnetization transfer (MT) or T 1 weighting.…”
Section: Methodsmentioning
confidence: 99%
“…In models of MS, MRI and histological iron distribution reveal that iron maintains myelin integrity and plays an important role in remyelination and repair [151]. Interestingly, age-related iron accumulation in the striatum is linked to demyelination and a reduction in declarative memory [152]. This indicates both a pathogenic and reparative role for iron in OL activity and integrity…”
Section: Poor Diet/nutritionmentioning
confidence: 99%